The Impact of Obesity on Endometrial Cancer: A Comprehensive Analysis - Agata Kolano; Anna Pejas; Szymon Markowiak; Marta Wardęszkiewicz; Wiktoria Jabłońska; Amelia Kasprzak; Maciej Świercz; Monika Truchta; Aleksandra Mańkowska (Kazimierz Wielki University, 2024)
Introduction and purpose: Endometrial cancer [EC] is the most common gynecological cancer in developed countries and its incidence is increasing worldwide. Obesity is a prominent risk factor associated with its incidence and progression. The aim of study: The article aims to provide a thorough explanation of the mechanisms through which obesity can contribute to the development of EC. Additionally, it emphasizes the crucial role of combating excess adipose tissue as a significant component of cancer prevention specifically targeting endometrial cancer. Material and method: ​​The literature review applied standard criteria and focused on PubMed articles using keywords: Endometrial cancer, Obesity, Mortality, Prevention, Pathogenesis Description of the State of Knowledge: Obesity significantly impacts EC development and prognosis, particularly in Type I cases. It modifies adipose tissue metabolism, affecting the release of various substances linked to tumor growth and mortality risk.The relative risks escalate with increasing BMI.  Following an EC diagnosis, higher BMI, especially ≥40, significantly associates with increased overall mortality risk. On a preventive front, exercise showcases its potential in reducing EC risk by moderating insulin and estrogen levels. Summary: These findings underscore the critical role of obesity in both EC development and prognosis, emphasizing the potential for preventive measures. Without proactive measures, the worldwide obesity epidemic will persist, exerting a substantial effect on EC occurrences.